2005
DOI: 10.1086/431722
|View full text |Cite
|
Sign up to set email alerts
|

Blueshifted [Oiii] Emission: Indications of a Dynamic Narrow-Line Region

Abstract: The [O III] λ5007 line is commonly used as an indicator of the systemic redshift of AGNs. Also, recent studies have used the width of this emission line as a proxy for the stellar velocity dispersion in the host galaxy. This paper calls both of these assumptions into question by analyzing a sample of approximately 400 AGN spectra from the first data release of the Sloan Digital Sky Survey. These spectra show that the low-ionization forbidden lines ([O II], [N II], [S II]) define a consistent redshift, but that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
166
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 18 publications
21
166
1
Order By: Relevance
“…The discrepancy remains high even when we account for a potential intrinsic offset Δσ = log(σ * )−log(σ [O iii] ) = 0.11 dex as reported by Ho (2009). However, the robustness of σ [O iii] as a surrogate for σ * is strongly debated as the scatter in the relation is much higher for σ [O iii] than for σ * (Shields et al 2003;Boroson 2005;Greene & Ho 2005a).…”
Section: Is He 2158−0107 An Outlier From the Bh-bulge Relations?mentioning
confidence: 96%
“…The discrepancy remains high even when we account for a potential intrinsic offset Δσ = log(σ * )−log(σ [O iii] ) = 0.11 dex as reported by Ho (2009). However, the robustness of σ [O iii] as a surrogate for σ * is strongly debated as the scatter in the relation is much higher for σ [O iii] than for σ * (Shields et al 2003;Boroson 2005;Greene & Ho 2005a).…”
Section: Is He 2158−0107 An Outlier From the Bh-bulge Relations?mentioning
confidence: 96%
“…Using a sample of ∼ 400 broad emission-line AGNs selected from the first data release of the SDSS, Boroson (2005) Figure 20 (upper panel). These so called "blue outliers" can provide a valuable tool in the study of the dynamics of NLR and its possible connection with other AGN components.…”
Section: Narrow Emission Linesmentioning
confidence: 99%
“…Nelson et al (2004) found a correlation between the blue asymmetry and Eigenvector-I space by studying the [O iii] λ5007 line profiles of the Palomar-Green quasars. The quasars associated with larger blue asymmetries tend to be stronger Fe ii emitters presumably having larger Eddington ratios (L/L Edd , where L Edd = 1.26 × 10 38 (M BH /M ) erg s −1 is the Eddington luminosity; see also Xu et al 2007;Boroson 2005;Greene & Ho 2005;Mathur & Grupe 2005 Bian et al 2005), but the correlation might not be real (e.g., Aoki et al 2005). Marziani et al (2003) pointed out that all the "blue outliers" have small Hβ line widths (<4000 km s −1 ) and high L/L Edd (see also Zamanov et al 2002;Komossa et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The spectroscopic monitor revealed a variability timescale from 1 to 10 years for the blue wings of the [O iii] λ5007 lines in two type I AGNs (IZW 1: Wang et al 2005;NGC 5548: Sergeev et al 1997), which means that the blue wings are likely emitted from the intermediate-line region located between the traditional broadline region and the NLR. In addition to the blue asymmetry, the redshifts of the [O iii] doublets are often found to be negative compared with the redshifts measured from both stellar absorption features and Hβ emission lines (i.e., [O iii] blueshifts; e.g., Phillips 1976;Zamanov et al 2002;Marziani et al 2003;Aoki et al 2005;Boroson 2005;Bian et al 2005;Komossa et al 2008). The rare cases of objects with strong [O iii] blueshifts larger than 100 km s −1 are called "blue outliers.…”
Section: Introductionmentioning
confidence: 99%